Strategic management of smart specialization in regional economic development: connection of export, sectoral, scientific, and technological competences - Lyshchikova, Julia; Stryabkova, Elena; Vladyka, Marina; Kulik, Anna; Bondareva, Yana (Nexo Revista Científica, 2023)
The article proposes a methodological approach to determining the priorities of smart specialization based on the conjugation of industry-specific specialization at the global, national, and macroregional levels and the scientific and technological competences of the region in the context of geographical, structural, technological, and cognitive proximity. As exemplified by the Central Black Earth macroregion, the study establishes a managerial matrix and scenario models based on competences. As a result of testing the research tools, a unified template of the managerial matrix for conjugating the directions of export (national, macroregional) and scientific and technological specialization of the macroregion was developed and scenario models for determining the priorities of smart specialization of regions within the Central Black Earth macroregion were built as part of entrepreneurial search procedures with the participation of all parties involved (regional authorities, business community, scientific community, and local residents). The proposed approach will allow all regions, including those not widely included in the global or national division of labor, to find a promising niche for development at the macroregional (local) level. In addition, it considers the possibilities of intersectoral convergence and the use of the accumulated competences of these regions in the field of end-to-end digital technologies.